Perundungan Dalam Drama The Glory Part 1: Kajian Pragmatik - Ittasaqa Maharani; Mei Solikhatul Latifakh; Salsa Rizkia Nurlaela; Anre Almanadaa; Asep Purwo Yudi Utomo; Didi Pramono; Rossi Galih Kesuma (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Perlocutionary speech is a speech that the deliverance is intended to influence the speech partners. In this research, an analysis of the form of perlocutionary speech contained in the drama "The Glory Part 1" is presented, which tells the story of a character named Moon Dong-eun who experienced bullying when she was in high school. Researchers chose to make the drama as a source of research data because the drama has a high level of popularity and contains a lot of power or perlocutionary speech effects. Hence, the research aims to reveal and describe the intent and ability or effect included in the drama. This research has two benefits, namely as a finding of the form of perlocutionary speech acts that can be applied as the material for expansion and strengthening in analyzing pragmatic studies. Then the second as a lesson for the community about the importance of maintaining speech in communicating to avoid the adverse effects of perlocutionary speech acts. The approach used in this research is divided into two, namely methodologically and theoretically. The methodological approach uses a qualitative descriptive approach, while theoretically, it uses pragmatic analysis. Further, the methods used are divided into three collections, data analysis techniques and data analysis result presentation techniques. Data collection techniques use listening and recording strategies, data analysis techniques use the equivalent method, and data analysis results in presentation techniques use informal methods. After conducting research, researchers found 34 results of perlocutionary speech acts with various forms of speech, such as threatening, frightening, degrading, harassing, humiliating, praising, granting requests, and fun, resulting in negative and positive effects on speech partners.